FUNDAMENTALS OF PEDAGOGICAL TRAINING: INSTRUCTIONAL STRATEGIES FOR EARLY LEARNERS (Scientific journal of the Fergana State University, 2025)
For educators who work with young children, effective pedagogical training is essential. In this article, we explore the core ideas that support successful instruction for early learners, stressing the value of a thorough understanding of child development and a variety of learning styles. We also look at important instructional strategies that are based on research-based best practices, such as play-based learning, differentiated instruction, and the thoughtful use of technology. We explore the practical applications of these strategies across various early childhood settings and stress the critical role of collaboration with families. By examining the interplay between theoretical frameworks and practical application, this article aims to give pre-service and in-service teachers the tools they need to design and implement engaging and developmentally appropriate learning experiences, ultimately maximizing the academic and personal growth of young children. The article emphasizes the importance of creating a supportive and inclusive learning environment that fosters both cognitive and socio-emotional growth..